Mussolini Italy's nightmare - Perkins, Jack, 1933-2019.; Schreiber, Liev.; Thompson, Molly; History Channel (Television network); Arts and Entertainment Network ([New York, N.Y.] : A&ETV, 2005)
Traces the life of Benito Mussolini, an Italian peasant who became one of the most feared dictators of the 20th century.
DVD.
Host, Jack Perkins ; narrator, Liev Schreiber.
Editor, Diane Vozza.
Originally shown on the television program Biography.
Keywords: Mussolini, Benito, -- 1883-1945.; Italy -- Politics and government -- 1914-1945.; Fascism -- Italy -- History -- 20th century; Heads of state -- Italy -- Biography